Mechanics of woven fabrics using cruciform elements - Ramgulam, Raj; Potluri, Prasad (European Journal of Computational Mechanics, 2005)
This paper presents a cruciform element for finite element modelling of woven fabrics. Unlike shell elements, cruciform elements do not need special forms near curved boundaries. Additionally, cruciform elements represent the discrete nature of textile structures and ensure that the arms of the cruciform are parallel to the warp and weft directions. In this paper, stiffness matrices for three types of loading, biaxial tensile, in-plane shear and in-plane bending, have been derived. FE modelling with cruciform elements has been demonstrated for bias extension of a woven fabric near the fixed clamp region.